The Effect of Combination Massage Frirage and Stretching on Increased The Range of Motion Shoulder Injury in Patients of Mco Yurigi - Al Jabar, M Irsyad; Sugiarto, Sugiarto; Sumartiningsih, Sri; Setiowati, Anies (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2023)
Limited range of motion of the shoulder joint due to injury can limit a person's activity. The purpose of this study was to determine the effect of a combination of frirage massage and stretching on increasing the range of motion of shoulder injuries in MCO Yurigi patients by providing treatment four times a meeting and eight times a meeting, and providing information to choose the right method to accelerate and increase the range of motion of shoulder injuries. This study used a quasi-experiment